Skin cancer prevention in the Polish population during the COVID-19 pandemic - Jęśkowiak-Kossakowska, Izabela; Calik, Jacek; Szeląg, Adam; Wiatrak, Benita (Frontiers in Public Health, 2025)
IntroductionIn addition to chronic skin inflammation, exposure to ultraviolet radiation (UVR) from sunlight is one of the most important factors predisposing to skin cancer. The aim of the study was to determine the occurrence of significant risk factors for skin cancer and to assess the methods of skin cancer prevention used in the Polish population during the COVID-19 pandemic.MethodsAn anonymous survey was conducted between December 2021 and December 2022. 651 respondents took part in the study, including 86 respondents (13.2%) suffering from skin cancer.ResultsIt was found that statistically significantly more often respondents with atopic dermatitis (p < 0.001), rosacea (p = 0.002), alopecia areata (p < 0.001), diabetes mellitus (p < 0.001), hypertension (p < 0.001), rheumatoid arthritis (p < 0.001) or Crohn's disease (p < 0.001) had skin cancer. Moreover, participants using medicines that could cause photodermatoses were more likely to suffer from skin cancer (p < 0.001), sunburn (p = 0.005) and have moles removed (p = 0.014) as well as more likely to have Sutton's nevus (p = 0.034) and Becker's nevus (p < 0.001). Skin cancer was diagnosed more often in participants with Celtic complexion (p < 0.001) and respondents with Celtic complexion were much more likely to have family members diagnosed with skin cancer (p = 0.014). The incidence of skin cancer (p < 0.001), Sutton's nevi (p = 0.007), Becker's nevi (p = 0.029) and mole removal (p < 0.001) increased with participant age. Women (p < 0.001) and respondents with Celtic and Northern European skin types (p < 0.001) most often choose creams with SPF50, but respondents with Southern European skin were the least likely to declare sunburn (p < 0.001). On sunny days more often, men (p < 0.001) and older respondents (p = 0.040) wear headgear and women wear sunglasses (p = 0.018). Women also supplemented vitamin D more often (p < 0.001). More women (p < 0.001) and younger respondents (p < 0.001) know the ABCDE method, which allows for quick identification of potential melanoma.ConclusionsRegular examination of moles, in addition to adequate skin protection against UVR, is an important element of skin cancer prevention, especially in people with fair skin, those suffering from inflammatory skin diseases and diabetes as well as taking medications with photosensitizing properties.